(untitled) (Research, Society and Development, 2021)
Objective: Validate the content of the Instrument for the Evaluation of Printed Educational Materials with focus on Health Literacy for Brazil (AMEELS-BR). Methodology: Descriptive methodological study, of the content validation type using Pasquali ´s methodology, carried out with 14 professors from the ​​health and pedagogy area, who evaluated the instrument´s items through an item-by-item classification using the Likert scale. The agreement between the judges was verified quantitatively through the Content Validity Index (CVI). Results: Of the 53 items that make up the instrument, 39 items obtained agreement within the established level (CVI >0.78), while 14 did not obtain the necessary agreement level, with CVI values ​​between 0.54 and 0.77. Thus, it was decided to reformulate the items that did not reach the necessary CVI. The final instrument had 55 items, as 02 items were subdivided, following the judges’ recommendation. As for the general assessment of the instrument, it resulted in CVI=0.81, when performed through the sum of all CVI calculated separately, divided by the number of items considered in the assessment. Therefore, the instrument presented the minimum agreement for verifying the validity of a new instrument, which should not be less than 0.8. Conclusion: The AMEELS-BR, in general, was considered valid in terms of its content by the expert panel, presenting a validity index within acceptable parameters and thus being able to be used by managers and health professionals for the evaluation and elaboration of the MEI.